2004
DOI: 10.1038/sj.ejcn.1601979
|View full text |Cite
|
Sign up to set email alerts
|

Occupational social class, educational level and area deprivation independently predict plasma ascorbic acid concentration: a cross-sectional population based study in the Norfolk cohort of the European Prospective Investigation into Cancer (EPIC-Norfolk)

Abstract: Objective: To investigate the independent association between three different measures of socioeconomic status and plasma ascorbic acid level. Design: Cross-sectional population based study. Setting and participants: 20 292 men and women aged 39-79 y who participated in the EPIC-Norfolk study. Results: Individuals in manual social classes, who had no educational qualifications or those who lived in the most deprived areas had significantly lower levels of plasma ascorbic acid compared to those in nonmanual soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 15 publications
1
22
0
2
Order By: Relevance
“…In the European Prospective Investigation of Cancer Norfolk study, individuals in manual social classes, or those who lived in the most deprived areas had significantly lower levels of plasma ascorbic acid compared to those in non-manual social classes, or who lived in less deprived areas. 3 Similarly, in a study conducted in the United Kingdom, plasma concentrations of vitamins C and B 12 , riboflavin, and beta-carotene were lower in the low-SES group than in the high-SES group. 4 The French EVA study showed a positive association between SES participants and their selenium and carotenoid status.…”
Section: Introductionmentioning
confidence: 94%
“…In the European Prospective Investigation of Cancer Norfolk study, individuals in manual social classes, or those who lived in the most deprived areas had significantly lower levels of plasma ascorbic acid compared to those in non-manual social classes, or who lived in less deprived areas. 3 Similarly, in a study conducted in the United Kingdom, plasma concentrations of vitamins C and B 12 , riboflavin, and beta-carotene were lower in the low-SES group than in the high-SES group. 4 The French EVA study showed a positive association between SES participants and their selenium and carotenoid status.…”
Section: Introductionmentioning
confidence: 94%
“…However, these criteria probably cover various risk factors, such as diet [75], the risk of infection and occupational exposure. Since these factors exist from childhood, they could have an impact on adult respiratory function [76].…”
Section: Social and Economic Factorsmentioning
confidence: 99%
“…Even if the sugary Astrofood breakfast were given to all students-affluent and low-income-the postprandial responses over time would likely differ. Evidence shows that the healthier background diets of affluent families would help buffer the effects of Astrofood; for example, several studies have shown that tissue levels of phytochemicals and antioxidants-the sort that would buffer the effects of inflammation and metabolic dysregulation-are higher in association with individual and neighborhood SES advantage [172][173][174][175][176][177][178]. Research has shown that neighborhood disadvantage is associated with lower diversity of the intestinal microbiome; the gut microbial ecology coincident with deprivation (mostly through ultra-processed dietary patterns) may play important roles in metabolic disturbances [179].…”
Section: Disadvantage Compoundedmentioning
confidence: 99%